Losses of essential oils and antioxidants during the drying of herbs and spices. A review - Prusinowska, Renata; Śmigielski, Krzysztof (Engineering Sciences And Technologies, 2015)
Drying is the most common and also the simplest method of preserving fresh plant materials. This process greatly extends the life of the product by the removal of water, which decreases the rate of chemical and enzymatic reactions, or even inhibits them. The drying step can cause a change in appearance, taste, color and consistency, as well as reduce the quantity of essential oils, polyphenols, pigments and vitamins. These changes can be significantly reduced by using suitable drying techniques, depending on the material. The choice of the technique should be based on knowledge of the biological, physical and chemical characteristics of the raw material. The paper presents the effects of drying on the quantitative loss of essential oils and compounds with antioxidant properties, as well as changes in the antioxidant properties of selected herbs and spices dried by different methods. Both, the food industry and the cosmetics or pharmaceuticals industry generates a demand for high-quality raw materials, and hence research is being conducted both on preservation methods and on their impact on the quality of the obtained material. It seems that the new technology of drying material in a fluidized bed, greatly reduces or even eliminates the disadvantages of current procedures
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2015, Nr 2 (17), s. 51-62
Keywords: drying; herbs; essential oils; polyphenols; suszenie; zioła; olejki eteryczne; polifenole